Xây dựng giải thuật và kiến trúc phần mềm tìm kiếm ảnh dựa trên tập các đặc trưng - Thắng, Huỳnh Quyết (VNU Journal of Science: Natural Sciences and Technology, 2004)
Content-based image retrieval, which provides convenient ways to retrieve images from large image databases, has been studied actively. We presented a software architecture which performs imagepresentatiog by the main featrures: color, histogram and colorshape. An algorithm to measuresimilarity of two image features base on the wavelet transform of the Histogram and Colorshape features and implementation results also presented.